Precision Crestec, Inc. industrial quality control study - Almada, Aleli Glaiza; De Villa, Ommaric; Limyu, Rey Jason (Diliman, Quezon City College of Engineering, 2005)
Quality is a very important aspect in every business and organization nowadays.It not only gives an edge to the company but is actually a mean for them to be able to stay in the market. A lot of studies have been made on quality. Different organizations, plans and principles have been developed to provide standards to improve and ensure quality. Precision Crestec Incorporated is one of the many businesses that keep track of their quality system to be able to stay ahead from their competitors and provide the best service to their customers. The company produces different boxes for different customers. The Pareto Diagram helped the group to determine the box or products were the company produces most defects. Company B was shown to have the most defective units produced. These are also the most critical to produce according to the QMD. Further analysis on the printer boxes data showed the major defects encountered by Precision Crestec Inc. which are Board Defects, Scum, Offsetting, Water Stain and Scratches. The group recommend that material planning and warehousing be evaluated since most of this top defects occur due to defective raw materials used in the production. Standards must also be set on the ink and water mixture to prevent defects such as water stain and scum. The working environment was also evaluated to provide a more effective, convenient and ergonomically designed workplace to the employees. This would improve productivity and efficiency. The working environment and the equipment must be well-maintained and kept clean at all times. Dirt that penetrates the machines produces defects that incur cost to the company. It was also observed that make-ready sessions are not so effective after all since from the data gathered by the group, a lot of defective units are still being produced during the first runs. Control Charts and Design of Experiments were used to analyze the problems identified such as the Color Density and the First-Runs Defects. A standard make-ready procedure was made to lessen defects during the first runs. The group also evaluated the sampling plan used by the company and from the analysis made they suggest the use of Continuous Sampling Plan since rectifying the inspection would notify the operator immediately of the defects produced. This is especially useful during the first runs. The company's quality recording system is not being implemented accordingly. Itemization and specification of the defects would help to provide the QMD as well as the Management with more valuable information with regards to their quality. Lastly the cost incurred to the company by the defective units produced and returned to them by their customers was analyzed. Since quality is an important consideration in every business, its cost (preventive costs, appraisal cost, internal and external failure cost) must be considered and be given due importance. Investing on quality is proven to benefit the company in the long run. Thus Precision Crestec must strength their existing quality system and invest on quality improvement activities. There is no loss on investing in a good quality system. And they should know that achieving quality is a continuous process and must be evaluated accordingly.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 135 : Industrial Quality Control
Keywords: Precision Crestec Incorporated; Manufacturing industries; Quality control